CORRELATIONAL ANALYSIS OF PRESERVICE ELEMENTARY TEACHERS’ LEARNING STYLES AND SELF EFFICACY ON THEIR CRITICAL THINKING SKILLS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2023)
As education systems are tasked with nurturing students' critical thinking skills to navigate an ever-evolving world, teacher education programs also grapple with the challenge of fostering critical thinking in preservice teachers. This article uncovers how the learning styles and self-efficacy of preservice elementary teachers shape their critical thinking skills. The results indicate that 86% of preservice elementary teachers have diverse learning styles and that these styles significantly influence their critical thinking skills. In conclusion, the alignment of appropriate learning styles can enhance the critical thinking skills of preservice elementary teachers, potentially shaping the critical thinking skills of their future students.
Keywords: learning styles; self-efficacy; local wisdom; critical thinking skills